Experimental and quantum chemical calculational studies on N-[4-(3-Methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-N?-pyridin-3ylmethylene-hydrazine - Saracoglu, Hanife; Cukurovali, Alaaddin (Wiley, 2012)
The title molecule, N-[4-(3-Methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-N'-pyridin-3ylmethylene- hydrazine (C20 H20 N4 S1), was characterized by 1H-NMR, 13C-NMR, IR, UV-visible, and X-ray determination. In addition to the molecular geometry from X-ray experiment, the molecular geometry, vibrational frequencies and gauge including atomic orbital 1H- and 13C-NMR chemical shift values of the title compound in the ground state have been calculated using the Hartree-Fock and density functional method (B3LYP) with 6-31G(d, p) basis set. The calculated results show that optimized geometries can well reproduce the crystal structural parameters. By using time-dependent density functional theory method, electronic absorption spectrum of the title compound has been predicted. (c) 2011 Wiley Periodicals, Inc.
Keywords: X-ray structure determination; IR spectra; NMR; DFT calculations; molecular electrostatic potential